2012
DOI: 10.1128/aac.00912-12
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Ranging Comparison of Rifampin and Rifapentine in Two Pathologically Distinct Murine Models of Tuberculosis

Abstract: dIn previous experiments, replacing the 10-mg/kg of body weight daily dose of rifampin with 7.5 to 10 mg/kg of rifapentine in combinations containing isoniazid and pyrazinamide reduced the duration of treatment needed to cure tuberculosis in BALB/c mice by approximately 50% due to rifapentine's more potent activity and greater drug exposures obtained. In the present study, we performed dose-ranging comparisons of the bactericidal and sterilizing activities of rifampin and rifapentine, alone and in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
126
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 41 publications
13
126
2
1
Order By: Relevance
“…Compared with rifampin, rifapentine has a longer half-life and lower minimum inhibitory concentration against M. tuberculosis (11)(12)(13)(14)(15). Preclinical studies using mouse models have shown that regimens containing daily rifapentine can cure TB after only 3 months of treatment (16)(17)(18). A phase 1 clinical trial showed that rifapentine doses up to 20 mg/kg administered daily were well-tolerated and safe in healthy volunteers (19).…”
mentioning
confidence: 99%
“…Compared with rifampin, rifapentine has a longer half-life and lower minimum inhibitory concentration against M. tuberculosis (11)(12)(13)(14)(15). Preclinical studies using mouse models have shown that regimens containing daily rifapentine can cure TB after only 3 months of treatment (16)(17)(18). A phase 1 clinical trial showed that rifapentine doses up to 20 mg/kg administered daily were well-tolerated and safe in healthy volunteers (19).…”
mentioning
confidence: 99%
“…Clinical trial simulations demonstrate that splitting the dose or taking the dose with food could substantially increase daily RFP exposures, which is a significant finding, given that RFP's activity appears to correlate best with AUC/MIC and that current dosing achieves concentrations that are still on the steep part of the dose-response curve. The dose-response relationship was reported in mouse studies (20), guinea pig studies (21), and patient early bactericidal activity studies (22). Most importantly, preliminary results from the recently completed phase IIb TBTC trial 29X in patients suggests a pronounced exposure-response relationship, where the time to culture conversion on solid and liquid media was best predicted by rifapentine exposure (23).…”
Section: Figmentioning
confidence: 96%
“…Mycobacterium tuberculosis strain H37Rv was used as a frozen stock prepared from a log-phase culture in Middlebrook 7H9 broth after mouse passage, and it was diluted in 7H9 broth before infection (12).…”
Section: Methodsmentioning
confidence: 99%